Creativity and disinformation in artificial intelligence-driven fashion communication - Sigita Kamašauskė; Živilė Sederevičiūtė-Pačiauskienė (Creativity Studies)
Fashion is an industry of constant changes and reflects societal alterations; therefore, fashion brands must always seek creative and innovative communication strategies for a positive brand reputation and be at the forefront of technology. Fashion communication shapes society’s needs and perceptions of reality, which are currently shifting due to the high density of various artificial intelligence technologies, including those that can recreate reality. Therefore, consumers are easy to deceive, and creative ways of communicating using artificial intelligence lead to creative ways of disinformation. The question arises as to which topics of creative use of artificial intelligence in the field of the fashion industry are the most widely studied and what the research gaps are. An integrative literature review focusing on papers published between January, 2016 and January, 2024 was conducted to answer the research question and clarify the tendencies of future research. The findings of this research show the emerging machine-washing concept as the topics that scholars are mostly focused on – the recreation of reality using deepfakes and altered images, digital influencers, and their messages.